Levels and Determinants of Complementary Feeding Pattern Exclusive of Minimum Meal Frequency and Dietary Diversity among Children of 6 to 23 Months in Bangladesh - Pervin, Naznin; Macer, Darryl; Lasker, Shamima P. (Bangladesh Journal of Bioethics, 2018)
Objective: To estimate the level of complementary feeding pattern (CFP) among children aged between 6 to 23 months and to identify the determinants in individual, household and community level in Bangladesh. Methods: From secondary data of Bangladesh Demographic Health Survey (BDHS) 2011 was used in this study. A total of 2,373 children aged between 6 to 23 months were selected. To estimate the level of CFP dimension index and the “score of the index” was used as dependent variables. Statistical analyses and tests were guided by the nature of the variables. Multivariable logistic regression analyses were performed to identify the significant determinants of CFP. Results: The overall level of CFP among children aged between 6 to 23 months was low. More than 95% of the children experienced inadequate (92.7%) CFP level. The mean levels of CFP as well as percentages of no or inadequate (94.1%) CFP were significantly lower among children of the youngest age group (06 months), uneducated parents, unemployed/laborer fathers, socio-economically poor families, food insecure families and rural areas. However, only few variables remained significant for adequate CFP in the multivariable logistic regression analysis. Adequate CFP was significantly lower among the children aged between 6 to 23 months (OR: 0.22, 95% CI: 0.10-0.47), children of illiterate fathers (OR: 0.32, 95% CI: 0.11-0.95) and socio-economically middle-class families (OR: 0.28, 95% CI: 0.09-0.86) as compared to their reference categories. Conclusion: Inappropriate and inadequate CFP may cause serious health hazards among children of 6 to 23 months in Bangladesh. It is ethical to take effective interventions and strategies by the government and other concerned stakeholders to improve the overall situation of CFP in Bangladesh.